Hazardous Household Substances: Alternatives That Are Relatively Free of Toxic Effects - Marie Hammer; Chris Koehler; Randall A. Cantrell (EDIS)
Some products that we use in our homes contain chemicals that are hazardous or toxic. We can reduce the potential for exposure to chemicals from household products and produce less hazardous household waste by using alternatives that are relatively free of toxic effects. This six-page fact sheet describes some alternatives that are relatively free of toxic effects. Written by Marie Hammer, Chris Koehler, and Randall Cantrell and published by the Department of Family, Youth and Community Sciences.http://edis.ifas.ufl.edu/he791